Neutralization of Soybean Oil Deodorizer Distillate for Vitamin Supplement Production - Cibelem Iribarrem Benites; Bruno Colling Klein; Soely Maria Pissini Machado Reis (International Journal of Chemical Engineering)
Soybean oil deodorizer distillate (SODD), a byproduct of the soybean oil refining process, is a complex mixture of compounds, such as free fatty acids (FFA), hydrocarbons, and sterols, such as tocopherols, a class of major natural antioxidants with vitamin E activity. As the utilization of SODD for tocopherol extraction is shown to be not economically viable, SODD in the semirefined form (neutral) is an interesting alternative to animal and possibly human diet enrichment. This study aimed to evaluate the SODD neutralization process varying the alkali (Na2CO3) concentration, temperature, and homogenization time. The optimal conditions for the neutralizing process, in order to obtain the greatest reduction in FFA content, the lowest leaching of tocopherols, and the greatest yield, were the following: Na2CO2 concentration of 4.34 N, temperature of 45.8°C, and homogenization time of 3 min 20 s. The FFA content was reduced from 53.4% to 6.1% after the initial neutralization, thus requiring a second neutralization step. The final FFA content was of 1.8% and total tocopherol (TT) accounted for about 11% of SODD.